Arab Nationalism: Past, Present, and Future - Robby, Hadza Min Fadhli (Center for Integrative International Studies Laboratory, Faculty of Political and Social Sciences, UIN Sunan Ampel Surabaya, 2020)
This article would like to discuss the development of Arab Nationalism throughout history. Arab Nationalism is discussed initially as a part of the resistance against Turkish and Ottoman power. The construction of enmity between Arab and Turkish nations became one of the most important features of Arab Nationalism. However, the enmity against the Turkish nation was not the only factor contributing to Arab Nationalism. The existence of the Arab nationalist movement and the rise of Arab intellectuals gave the momentum for Arab nationalism to obtain a prominent place. As Arab nations declared their independence, there are aspirations that seek Arab nations to be united into one country. One such idea was brought up by Gamal Abdel Nasser, previously the President of the Arab Republic of Egypt. Arab Nationalism experienced its hey-day during these days, but soon after, it loses its charm after the war with Israel. This paper will also discuss the problems and reasons behind the decline of Arab Nationalism.